Maxillary full‐arch reconstruction using a sequenced digital workflow. Issue 4 (18th May 2020) - Roberts, Matt; Shull, Franklin; Schiner, Brit
Abstract: Objective: Multi‐staged treatment of a terminal maxillary arch from tooth‐supported provisional to implant‐supported final reconstruction using a fully digital workflow is reported. Each stage of the phased esthetically‐guided reconstruction treatment plan, provisional restorations, and final restoration were executed in a virtual 3D environment prior to clinical treatment, providing CAD/CAM manufactured precision provisionals and final restoration that preserved the natural gingival architecture, function, and esthetics demanded by the patient. Demonstrate the efficacy of using a digital workflow to fully restore a terminal maxillary arch with a precision implant‐supported final prosthetic by instituting a multi‐phase treatment plan designed to preserve the patient's gingival architecture, facial esthetics, and natural function. Clinical Considerations: Sophisticated digital tools and software allow the dental team to work in a virtual environment to envision and execute the outcome of each stage of treatment prior to the patient appointment and to deliver an esthetically‐guided precision final prosthesis that replicates the form, function, and occlusion of existing natural teeth. Conclusions: Digital technologies provide clinicians and dental ceramists with sophisticated tools and software that advance the precision and execution of each phase of maxillary arch reconstruction in fewer patient visits and elevate the patient experience and treatment outcome. Clinical Significance: Sophisticated digital tools and software allow the dental team to work in a virtual environment to envision and execute the outcome of each stage of treatment prior to the patient appointment and to deliver an esthetically‐guided precision final prosthesis that replicates the form, function, and occlusion of existing natural teeth.